2009
DOI: 10.1371/journal.pone.0006706
|View full text |Cite
|
Sign up to set email alerts
|

Highly Pathogenic Avian Influenza Virus Infection of Mallards with Homo- and Heterosubtypic Immunity Induced by Low Pathogenic Avian Influenza Viruses

Abstract: The potential role of wild birds as carriers of highly pathogenic avian influenza virus (HPAIV) subtype H5N1 is still a matter of debate. Consecutive or simultaneous infections with different subtypes of influenza viruses of low pathogenicity (LPAIV) are very common in wild duck populations. To better understand the epidemiology and pathogenesis of HPAIV H5N1 infections in natural ecosystems, we investigated the influence of prior infection of mallards with homo- (H5N2) and heterosubtypic (H4N6) LPAIV on expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
117
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(125 citation statements)
references
References 26 publications
(38 reference statements)
7
117
1
Order By: Relevance
“…Ots et al 1998;Forsman et al 2008). In particular, prior exposure to an HA-homologous virus of LPAI phenotype has been shown to be sufficient to reduce clinical symptoms and viral shedding (Fereidouni et al 2009). Even prior infection with an HA-heterologous virus may result in partially reduced symptoms and viral shedding (Fereidouni et al 2009;Jourdain et al 2010).…”
Section: Does Infection Occur At Random or Only In Certain Individuals?mentioning
confidence: 99%
See 3 more Smart Citations
“…Ots et al 1998;Forsman et al 2008). In particular, prior exposure to an HA-homologous virus of LPAI phenotype has been shown to be sufficient to reduce clinical symptoms and viral shedding (Fereidouni et al 2009). Even prior infection with an HA-heterologous virus may result in partially reduced symptoms and viral shedding (Fereidouni et al 2009;Jourdain et al 2010).…”
Section: Does Infection Occur At Random or Only In Certain Individuals?mentioning
confidence: 99%
“…from Asia to Australia), the phenomenon of partial crossprotective immunity increases the potential for migrants to disperse HPAI over large distances. To date, most infection experiments have been conducted with seronegative birds; the studies by Fereidouni et al (2009) andJourdain et al (2010) highlight the importance of including infection history in the design of experiments.…”
Section: Does Infection Occur At Random or Only In Certain Individuals?mentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, Kalthoff et al (2008) showed that naïve mute swans died shortly after infection with HPAI H5N1 but those with previous exposure to LPAI viruses were able to survive without apparent symptoms. Fereidouni et al (2009) also showed that prior infection with low pathogenic H5N2 provided homosubtype immunity against HPAI H5N1 in waterfowl. These studies imply that previous infection with LPAI virus effectively reduces susceptibility of the host to infection and decreases transmission of HPAI virus, affecting the course of HPAI not only clinically, but also epidemiologically.…”
Section: Introductionmentioning
confidence: 86%